Combined action of inner and outer steel tube on the ultimate bearing state of steel-concrete composite. Issue 1 (31st December 2022) - Touogam Touolak, Bénédicte
Abstract: The question of the thickness and diameter report on the performance of the structures is approached in detail in this scientific work. This paper focuses on the stress-strain characteristics, geometry imperfections, damage and deformations that occur inside the materials structure properties. Finite element analysis and experimental results show that, as loading progressed, the strain distribution in the shaft lining structure became approximately uniform indicating the formation of a tied arch mechanism. Concrete strain distribution is nonlinear and non-conform to Bernoulli's assumptions for strain and stress distribution; this nonlinearity is due to the shear deformations inside the structural element. The study can provide certain reference for practical engineering calculation.